PENGARUH PERKEMBANGAN TEKNOLOGI, MEDIA SOSIAL, HARGA, DAN LOKASI TERHADAP PENDAPATAN UMKM DI KOTA LANGSA: MENGEKSPLORASI DINAMIKA SUKSES BISNIS DI ERA DIGITAL - Ulfa, Maria; Kurlillah, Anis; Pospos, Ade Fadillah FW; Budiman, Iskandar (Faculty of Islamic Economic and Business (FEBI), Sayyid Ali Rahmatullah State Islamic University (UIN SATU) Tulungagung, 2024)
This study aims to determine the influence of each variable, namely technological development, social media, price, and location on the income of micro, small, and medium enterprises (MSMEs) in the city of Langsa. The method used is quantitative with multiple regression analysis. The population in this study is micro, small, and medium enterprises (MSMEs) in Langsa City totaling 24,684 units. The sampling technique in this study uses Proportionate Stratified Random Sampling technique with a total of 100 respondents. Based on the test results, the Social Media and Location variables have a significant effect on MSME Income in Langsa City, while Technological Development and Price variables do not have a significant effect on MSME Income in Langsa City. Meanwhile, for the simultaneous test results presented, it can be seen that the Ftest value is 25.810 > the value of Ftable (2.70) and significant at 0.000 < 0.05. Therefore, it can be concluded that the four independent variables, namely Technological Development, Social Media, Price, and Location, simultaneously have a positive and significant effect on MSME Income with an adjusted coefficient of determination (adjusted R2) obtained at 0.446. This indicates that the variables of Technology, Social Media, Price, and Location are able to explain 44.6% of the variation in MSME Income, while the remaining 55.4% is influenced by other variables not examined in this study.